Assessing the combined effect of the diffusion of solar rooftop generation, energy conservation and efficient appliances in households. (20th September 2017) - Cardenas, Laura; Zapata, Manuela; Franco, Carlos Jaime; Dyner, Isaac
Abstract: There is a growing worldwide concern regarding emissions of energy-related greenhouse gases (GHGs). Policy, technology and human awareness provide opportunities for offsetting these effects through energy conservation, efficient appliances and solar generation in households as these have been the subject of increasing attention across the world in recent years. Solar rooftop generation, in particular, could deliver significant efficiency improvements and reductions of CO2 emissions through its diffusion, which also avoids losses in electricity transmission and distribution systems; energy efficiency contributes to the achievement of a sustainable future because it reduces the energy-infrastructure needs, increases competitiveness and improves consumer welfare; conservation would also reduce CO2 emissions in households. The purpose of this paper is to assess the combined effect of the diffusion of solar rooftop generation, energy efficiency and electricity conservation in the residential sector in Colombia. Simulation results for different policy scenarios indicate that rooftop generation, energy efficiency and conservation can together lead, under certain conditions, to important reductions in both electricity prices and emissions. Highlights: Households can make important reductions in greenhouse gas emissions. An SD model is formulated to assess the effect of emissions abatement. Rooftop PV, efficient appliances and energy conservation policies are modelled. A combination of policies can achieve great reductions in emissions and prices.